The Legitimacy of the Protected Domain in the 2005 Constitution of the Republic of Iraq between the Requirements of Protection and the Imperatives of Development: A Comparative Study - Hussein, Osamah (Journal of Legal Sciences, 2026)
This study examines the constitutional legitimacy of the protected domain in the 2005 Constitution of the Republic of Iraq, focusing on the tension between constitutional protection and the requirements of constitutional development. It proceeds from the assumption that constitutions embody a core constitutional structure that defines the identity of the constitutional order and sets substantive limits on the scope of constitutional amendment. Adopting an analytical and comparative methodology, the study explores the theoretical foundations of the protected domain and draws on comparative constitutional experiences, particularly those of India and Germany. It then analyzes the Iraqi constitutional framework, highlighting the absence of an explicit constitutional provision on the protected domain and the lack of practical experience with constitutional amendment. The study concludes that, notwithstanding this absence, the protected domain enjoys normative legitimacy derived from foundational constitutional principles; however, it requires further conceptual and institutional clarification to ensure constitutional stability while allowing for constitutional evolution.